Sustaining Prater Park : UNESCO World Heritage Site Proposal - Mumford, Karen G.; Oberly, James Warren, 1954-; Olm, Jill; Rohlik, Brittney; Westphal, Alyssa; Moschkau, Clarissa (My University, 2018)
This proposal advocates for Prater Park in Vienna, Austria to receive the UNESCO (United Nations Educational, Scientific and Cultural Organization) World Heritage site designation. The proposal highlights UNESCO’s designation criteria as demonstrated in the physical environment and social use of the space. Through examination of the historical and contemporary uses of Prater Park, the student research team made strong connections to UNESCO World Heritage’s mission. Visiting Vienna during summer of 2016, the team was able to investigate firsthand the Viennese atmosphere and values reflected in the park.
Color poster with text, photos, and map.
Keywords: Prater Park (Vienna, Austria); World Heritage sites; UNESCO; Posters